Epidemiological characteristics of mild traumatic brain injuries in Iceland : an exploratory study of the adult general population - Eyþór Atli Aðalsteinsson 2000-; Hugi Garðarsson 1982- (2024)
This exploratory study used a self-report survey to examine the epidemiology of mild traumatic brain injury among the Icelandic adult general population while accounting for demographic variables. Additional objectives included investigating mechanisms of injury and the type of care sought post-injury. A convenience sample of 1366 participants aged 18-65 (M = 40.4, SD = 12.9) provided valid answers. The gender distribution was 55.4% females, 44.3% males. Participants with a history of participating in high-risk sports were excluded from the sample. 59.4% self reported having sustained mild TBI at least once, and 40.3% self-reported no injury. Males were more likely to self-report mild TBI than females, with 64.3% compared to 55.6%. Increased age was associated with a higher prevalence of mild TBI. Falls were the most common cause of mild TBI among all age groups except for the youngest, whereas sports were the most common cause for them. Keywords: mild TBI, epidemiology, self-report survey, Iceland general public. Markmið þessarar rannsóknar var að varpa ljósi á algengi heilahristings á meðal almennings og hvort bakgrunnsbreyturnar aldur, kyn og menntunarstig hefðu áhrif á algengið. Einnig voru helstu orsakavaldar heilahristings kannaðir, sem og hversu langt hafði liðið frá síðasta heilahristing og hversu margir höfðu leitað sér aðhlyningar. Rannsóknin innihélt hentugleikaúrtak sem samanstóð af 1366 þátttakendum sem voru á aldrinum 18-65 ára (M = 40,4, SF = 12.9) og höfðu ekki tekið þátt í íþróttum þar sem áhætta á heilahristing er mikil. Niðurstaða rannsóknarinnar var að 59,4% þátttakenda greindu frá heilahristing einhverntímann á lífsleiðinni. Karlmenn voru líklegri en konur til að greina frá heilahristing, en 64,3% karlmanna svöruðu játandi á meðan 55,6% kvenna svöruðu játandi. Jákvætt samband var á milli aldurs þátttakenda og fjölda heilahristinga. Neikvætt samband var á milli menntunarstigs og algengi heilahristings. Föll voru algengasta orsök heilahristings á meðal allra aldurshópa fyrir utan þann ...